Analysis of Product and Digital Marketing on Brand Image and Its Impact on Purchase Decisions of Muslim Fashion Products in The Ciayumajakuning Region (Cirebon, Indramayu, Majalengka, Kuningan) - Sudadi Pranata; Amroni; Oryz Agnu Dian Wulandari; Feri Fauzi (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
The role of product quality and digital marketing is crucial in shaping a strong brand image for Muslim fashion companies in the Ciayumajakuning region (Cirebon, Indramayu, Majalengka, Kuningan). High-quality products and effective digital marketing can influence consumers' perceptions of the brand. This study aims to examine in depth the impact of product quality and digital marketing on brand image and its effect on purchasing decisions for Muslim fashion products in Ciayumajakuning. The study involved a sample size of 125 respondents and utilized SEM PLS as the analytical tool. The results show that product quality has a significant influence on brand image, digital marketing strongly affects brand image, and brand image significantly impacts purchasing decisions.